What are these results telling me? - Scicluna, Elizabeth Anne (International Journal of Infection Control, 2012)
The scientific community must be able to read the published literature with a critical eye and look for the relevant information in the paper to see if they come up with the same conclusions as the authors. They should be aware of possible sources of bias and have enough information about the surveillance system used to collect the data. They should also be aware that meta-analysis is affected by publication bias and the reader should be able to determine how the authors selected the articles for their meta-analysis and if any conflict of interest present in the original papers have been reported. Several tools/checklists and guidelines were issued to ensure that the published data is accurate and reliable.